Analisis Manajemen Keuangan Perguruan Tinggi Ditinjau Dari Uang Kuliah Tunggal (UKT)Di Perguruan Tinggi - Ahmad, Ahmad (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Education is the right of every citizen that meets nationalstandards for one of the standard cost of education.To meet the demandsof the government issued a policy on Single Tuition, thus opening spacefor state and private universities to set tuition independently, so thequestion arises , why the cost of college in Indonesia has not beenstandardize while increasing education costs each year? This researchuses a qualitative approach with a survey method at universities inIndonesia from February 2013 until December 2013. The data analysistechniques were used descriptive analytical method, with the followingrecommendations: 1) The goverment should standardize the cost of acollege education in Indonesia based on the location of the region,income level, and the quality of higher education. 2) The governmentshould control the extra funding of universities in Indonesia with theprinciple that education funds that are transparent, accountable ,effective and efficient, 3) The Government should develop guidelines andoperational technical guidance before issuing any policy,4)Thegovernment should do evaluation of financing higher education on aregular basis to improve the management of standardized education, 5)Higher education should be democratic and transparent in themanagement of higher education, and 6) Active community participationshould be increased in escorting management colleges, and universitiesare part of the contributing greatly to the college .Keywords: standard of higher education, single tuition